A Retrospective Study of the Effectiveness of Four Different Treatments of Periodontal Disease in Equine Cheek Teeth. (June 2016) - Jackson, Kirsten; Weber, Lukas M.; Tennant, Marc
Periodontal disease of equine cheek teeth is common and may lead to tooth loss if left untreated. Limited information is available comparing the effectiveness of treatment methods. The objective of this study was to retrospectively compare the effectiveness of 4 commonly used treatments in reducing periodontal pocket depth (in addition to routine dental treatment and occlusal equilibration). The 4 treatments compared were (1) removal of feed material, lavaging the pocket with dilute chlorhexidine, and then rinsing the mouth with chlorhexidine-containing mouthwash (CL); (2) CL plus placement of metronidazole into the pocket (M); (3) M plus the addition of polyvinyl siloxane temporary filling over the diastema (PVS); and (4) diastema widening to increase the interdental space, then PVS (DW). Pocket measurements were compared before and 2 to 6 months after treatment. Treatment groups CL, M, and PVS showed statistically significant reductions in pocket depth following treatment. The mean pocket depth reduction was the greatest in the DW group (and this was the only group with no cases having an increase in pocket depth), but this was not significant due to the small sample size. Additional analysis to compare effectiveness revealed a confounding effect of initial pocket depth. After accounting for this, DW was associated with smaller improvements than the other treatments, however, this was also based on a small sample size. After accounting for confounders, differences between treatments CL, M and PVS were not found to be significant, although all were associated with statistically significant reductions in pocket depth.